Efecto de medios audiovisuales en mejora de la conciencia ambiental en alumnos de 1ero de secundaria colegio 60024 Iquitos 2022 - Uribe Flores, Jory Prisscilla (2023)
The work was developed in Saint John the Baptist district, in the National School 60024, with the objective of determining the efficiency of the audiovisual materials to improve the environmental conscience in the students, the population conforms it the students of the 1ero of secondary in total 90 both sexes, the sample was 30 students from the section TO day shift, for the analysis of the data you hiso use of the SPSS, and the calculation leaf Excel. Being reached the conclusion: The means visual audio are tools that you/they help to improve the learning. The efficiency in the aspect Cognitivo and Affective it is like the is indicated (83.3%) he/she responded it doesn't exist subject that talks about this topic, the (100%) he/she wants to participate in environmental topics, the (100%) he/she wants to work more in these topics, the (100%) they wanted that in the subjects audiovisual means are used, to the (100%) they would like to have contact with the nature, the (100%) he/she says that to throw the waste to the floor is not well, to the (90%) he worries about the destruction of the atmosphere and to the (100%) they would like to receive more information through audiovisual means. In the dimensions Conativa and it Activates the (60%) he/she says that to work in team makes it feel well, to the (70%) he would like to be part of a club environmentalist, to the (73.3%) he likes documental that speak on the nature and to the (86.7%) he likes to talk about the nature, the (73.3%) they feel responsible for the environmental deterioration, the (63.3%) he/she says that their educational center should play more environmental topics, the (46.7%) recyclable material reutilizing, the (100%) it uses the water and the responsibly (100%) it deposits its residuals in appropriate places of storing.